Tinjauan Pencahayaan Buatan Dalam Membangun Suasana Ruang Pada Pameran Tematik - Ghunadi, Galih; Fatimah, Dina (Fakultas Desain Universitas Komputer Indonesia, 2021)
This study aims to present a review of artificial lighting that contradicts the thematic concepts presented by the exhibition so that it can bring up or build the atmosphere and character of its own space. Lighting is one of the binding elements of space that has an important function in illuminating an object or human activity. As the times evolve, the demands of human activity are more complex and dynamic. So it requires adjustments to the lighted object. The other function is to form perspective, color and spatial composition. For example, natural light sources are inefficient if used in the long run. so this affects the effectiveness in its use. another case with artificial light sources that are generally used indoors, with light sources that can be controlled by humans, making it more effective and efficient utilization. he method used in this research is descriptive analysis with qualitative data. From the results of the analysis in the case study of the Museum of Wildlife Jatim Park 2 shows that, the design of artificial lighting and the use of colors that focus on environmental recognition (environment) or the habitat of each animal, can provide a specific character and atmosphere of the space, so that the concept of the theme and storyline presented by the exhibition can be conveyed to visitors.